Methodological Aspects of Elaborating Marketing Strategy of Innovation Bank Products and Services - N. I. Bykanova (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
Today the key factor of influencing banking sector is the development of information systems and overall strategy of economy digitalization as its consequence. On today’s competitive banking market we can observe the necessity to elaborate and promote approaches to banking product and service marketing that are meant to provide finance stability of banking business and orientation of marketing innovation bank functioning not only to their opportunities but also to market needs. In spite of a big number of publications dealing with this issue, academic research should be developed further. In research by Russian scientists there are actually no developments dealing with the problem of finding structural components for elaborating marketing strategy of banking products and services. Insufficient attention was paid to approaches of defining the essence of banking product and service marketing. The problem of assessing the level of the impact of banking innovation marketing on competitive positions and finance stability of banks has not been settled yet. The article showed components necessary to elaborate strategy of banking product and service marketing, among which the author underlined their characteristics depending on the model of commercialization, sub-system of their implementation process and interconnection between the chosen marketing strategy and classification features of banking innovation. The author designed a structural and logical scheme of elaborating strategy of baking product and servicer marketing and formulated its definition.